Nanogold(0)-Catalyzed Addition of Heteroelement σ Linkages to Functional Groups - Stratakis, Manolis; Lykakis, Ioannis N. (Synthesis, 2019)
In recent years, supported Au nanoparticles and nanoporous Au materials have shown remarkable catalytic activity in the activation of σ heteroelement linkages such as, Si–H, Si–Si, B–B and B–Si, and their subsequent addition to functional groups, primarily π bonds. In this review article we discuss the reaction modes known to date, and attempt to discuss the mechanistic clues of these transformations which are rather unexpected in terms of conventional transition-metal catalysis concepts, given that the catalytic sites are metallic Au(0).1 Introduction2 Activation of Hydrosilanes2.1 Reactions of Hydrosilanes with Alkynes2.1.1 Hydrosilylation2.1.2 Dehydrogenative Coupling2.2 Reactions of Hydrosilanes with Allenes2.3 Reactions of Hydrosilanes with Carbonyl Compounds and Imines2.4 Reactions of Hydrosilanes with α-Diazo Carbonyl Compounds2.5 Miscellaneous Transformations from the Nano Au-Catalyzed Activation of Hydrosilanes3 Activation of Disilanes3.1 Disilylation of Alkynes3.2 Reactions of 1,1,2,2-Tetramethyldisilane with Alkynes4 Activation of Diboranes4.1 Diborylation of Alkenes4.2 Diborylation of Alkynes4.3 Diborylation of Allenes4.4 Diborylation of Methylenecyclopropanes5 Activation of Silylboranes5.1 Silaboration of Alkynes5.2 Silaboration of Allenes5.3 Silaboration of Unactivated Epoxides and Oxetanes5.4 Reactions of Silylboranes with Aromatic Carbonyl Compounds6 Conclusions and Future Perspectives
Keywords: Au nanoparticles; nanoporous Au; heterogeneous catalysis; hydrosilylation; disilylation; diborylation; silaboration